Heterologous expression and characterization of a cold-adapted endo-1, 4−β−glucanase gene from Bellamya chinensis laeta. (November 2018) - Ueda, Mitsuhiro; Konemori, Yuta; Nakazawa, Masami; Sakamoto, Tatsuji; Sakaguchi, Minoru
Graphical abstract: Highlights: A cold-adapted endo-1, 4-β-glucanase from Bellamya chinensis laeta (BC-EG70a) was expressed in Pichia pastoris . The optimum pH and temperature of rBC-EG70a mature and CatD were the same. At lower temperature (30 °C), the specific activity of rBC-EG70amature toward soluble cellulose was 5 to 20-fold higher than those of fungal cellulases. rBC-EG70acatD demonstrated higher activity than rBC-EG70amature in the ethanol solutions. It was suggested that rBC-EG70a are able to apply the SSF process. Abstract: An endo-1, 4-β-glucanase from Bellamya chinensis laeta (BC-EG70a) was expressed in Pichia pastoris GS115. The molecular masses of the mature recombinant BC-EG70a enzyme (rBC-EG70amature ), the rBC-EG70a catalytic domain (rBC-EG70aCatD ), and the rBC-EG70a cellulose binding domain (rBC-EG70aCBD ) were 65 kDa, 50 kDa, and 15 kDa, respectively. While the optimum pH and temperature of rBC-EG70amature and rBC-EG70aCatD were pH 5.5 and 50 °C, rBC-EG70amature was more stable within a range of pHs and temperatures compared to rBC-EG70aCatD . The major hydrolysis products from cellohexaose using rBC-EG70amature and rBC-EG70aCatD were cellobiose and cellopentaose during the early stages of the hydrolysis reaction. At lower temperature (30 °C), the specific activity of rBC-EG70amature using carboxymethyl cellulose as the substrate was 5 to 20-fold higher than those of Trichoderma reesei and T. viride cellulases. rBC-EG70acatD demonstrated higher activity than rBC-EG70amature in 10%, 15%, and 20% (v/v) ethanol solutions. rBC-EG70aCBD showed specific adsorption toward Avicel, powder cellulose, and phosphoric acid swollen cellulose.